Event power how global events manage and manipulate - Rojek, Chris (SAGE, 2013)
Argues that events are essential elements in corporate-state partnerships of 'invisible government' that have revived the romance of charity so to form illusory communities, while cloaking power imbalances and social inequalities.... [an] account of communication power, social ordering and control. -- Page [4] of cover.